2021
DOI: 10.1002/adfm.202010929
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances for Improving Functionality, Biocompatibility, and Longevity of Implantable Medical Devices and Deliverable Drug Delivery Systems

Abstract: The great majority of medical devices elicit foreign body response (FBR) postimplantation. FBR is a major hurdle to develop a successful device for impaired organs, leading to failure of devices/treatments. In recent times, several advantageous technologies have been developed based on either surface modifications or localized drug delivery systems (DDSs) in order to overcome the FBR limitation, which enhanced the success of implantable medical devices. The recent advances for improving the functionality, bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 123 publications
(286 reference statements)
0
13
0
Order By: Relevance
“…b) J versus voltage and c) C versus frequency at various strains. d) Comparison of the (PU + /PU − )3 nanodielectrics in this study with other previously reported flexible dielectrics in literature. e) Schematic of the fabrication procedure for the stretchable capacitors from (PU + /PU − ) 3 nanofilms.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…b) J versus voltage and c) C versus frequency at various strains. d) Comparison of the (PU + /PU − )3 nanodielectrics in this study with other previously reported flexible dielectrics in literature. e) Schematic of the fabrication procedure for the stretchable capacitors from (PU + /PU − ) 3 nanofilms.…”
mentioning
confidence: 76%
“…The emergence of internet of things or artificial intelligence calls for frequent human–machine interactions in daily lives through flexible/stretchable electronics, such as pliant touch screens, conformable sensors, and implantable medical devices. [ 1–3 ] In order to be compatible with these devices, field‐effect transistors (FETs), conventionally used for analog amplification or digital logics, are required to be redesigned or reengineered with robust electronic materials and structures to suit for device deformation in the usage. Recent decade has witnessed the progress in the field of flexible electronics to meet such demands.…”
Section: Introductionmentioning
confidence: 99%
“…A broad spectrum of carriers has been widely reported, from single polymer or mixture of polymers, 4,5 up to liposomes 2 and lipids 4 . The main functionalities and major advantages of these carriers are holding the drug mechanically, preserving its chemical stability, and regulating its release kinetics 1,3,6 . However, as for each carrier‐based release mechanism, we can point few disadvantages, including material‐induced inflammation resulted from the immune‐system foreign body response (FBR) to the carrier material, 7,8 as well as the limited drug dose that can be loaded within the DDS, 6 among others.…”
Section: Figurementioning
confidence: 99%
“…carrier-free drug delivery systems, drug crystals, medical applications, polymers Targeted and controllable drug release via carrier-based drug delivery systems (DDSs) have been widely investigated. 1,2 This method is based on transporting pharmaceutical cargo to a specific target organ, 2,3 usually by loading it into a carrier. 2,4,5 A broad spectrum of carriers has been widely reported, from single polymer or mixture of polymers, 4,5 up to liposomes 2 and lipids.…”
mentioning
confidence: 99%
“…40 Further, various silicone surface modification techniques have been used to reduce the complications from silicone‐based medical devices. 23 , 34 , 41 , 42 , 43 , 44 , 45 Nevertheless, few studies have researched silicone implant surface modification using hASCs to reduce breast capsular contraction. Barr et al reported that a biomimetic breast adipose tissue‐derived breast implant surface could effectively decrease the inflammatory phase of the implant‐driven foreign body reaction related to capsular contracture in vitro.…”
Section: Introductionmentioning
confidence: 99%